Diagnostic criteria for constitutional mismatch repair deficiency syndrome: suggestions of the European consortium 'Care for CMMRD' (C4CMMRD). Issue 6 (15th April 2014) - Wimmer, Katharina; Kratz, Christian P; Vasen, Hans F A; Caron, Olivier; Colas, Chrystelle; Entz-Werle, Natacha; Gerdes, Anne-Marie; Goldberg, Yael; Ilencikova, Denisa; Muleris, Martine; Duval, Alex; Lavoine, Noémie; et al.
Abstract : Constitutional mismatch repair deficiency (CMMRD) syndrome is a distinct childhood cancer predisposition syndrome that results from biallelic germline mutations in one of the four MMR genes, MLH1, MSH2, MSH6 or PMS2 . The tumour spectrum is very broad, including mainly haematological, brain and intestinal tract tumours. Patients show a variety of non-malignant features that are indicative of CMMRD. However, currently no criteria that should entail diagnostic evaluation of CMMRD exist. We present a three-point scoring system for the suspected diagnosis CMMRD in a paediatric/young adult cancer patient. Tumours highly specific for CMMRD syndrome are assigned three points, malignancies overrepresented in CMMRD two points and all other malignancies one point. According to their specificity for CMMRD and their frequency in the general population, additional features are weighted with 1–2 points. They include multiple hyperpigmented and hypopigmented skin areas, brain malformations, pilomatricomas, a second childhood malignancy, a Lynch syndrome (LS)-associated tumour in a relative and parental consanguinity. According to the scoring system, CMMRD should be suspected in any cancer patient who reaches a minimum of three points by adding the points of the malignancy and the additional features. The diagnostic steps to confirm or refute the suspected diagnosis are outlined. We expect that application of the suggested strategy for CMMRD diagnosis will increase the number of patients being identified at the time when they develop their first tumour. This will allow adjustment of the treatment modalities, offering surveillance strategies for second malignancies and appropriate counselling of the entire family.